(untitled) (Journal of Hama University, 2025)
The huge increase in traffic due to an increase in the users number and introduction of the high bits rate made the adaptive antennas use an urgent necessity with the high implementation of the radio communications. This type of the antennas that called smart antennas combines the antenna matrix and digital signal processing capability. These antennas modify their transmission format to direct the main lope to the desired direction and simultaneously shape null towards the interfering signal. This system also distinguishes the returning signals combinations from different directions and then increases the receiving power of the desired user. This research studied adaptive beamforming using an LMS algorithm that is simple and low in computational complexity which makes it suitable for real time applications. This research also focused on studying the elements number impact of the antenna matrix on beamforming, as well as comparing these antennas performance for different distances of wave length between antenna elements.